High-compaction-density porous silicon-carbon composite material as well as preparation method and application thereof

By preparing a high compaction density porous silicon-carbon composite through dealloying and carbon-coating, the issues of low compaction and volume expansion in silicon-based electrodes are addressed, resulting in improved energy density and stability.

CN119230785AActive Publication Date: 2024-12-31HEBEI UNIV OF TECH

Patent Information

Application Number
CN202411434775.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-31
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

Existing silicon-based negative electrode materials for lithium-ion batteries face issues of low compaction density, high specific surface area, and volume expansion leading to electrochemical failure and reduced cycle life, while nano-sized silicon materials are costly and have low compaction density.

Method used

A method involving dealloying micron silicon to create a porous skeleton, filling it with nano-silicon, and carbon-coating to form a high compaction density porous silicon-carbon composite material.

Benefits of technology

The method significantly increases compaction density, improves volume energy density, and enhances cycle stability and conductivity, maintaining high capacity retention rates and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230785A_ABST
    Figure CN119230785A_ABST
Patent Text Reader

Abstract

The invention discloses a high-compaction-density porous silicon-carbon composite material and a preparation method and application thereof, and the preparation method comprises the following steps: step 1, carrying out dealloying treatment on a micron silicon-based material to obtain a porous silicon skeleton; 2, filling pores, and filling the pores formed by the silicon-based material with a nano silicon material to obtain an intermediate product; and step 3, carrying out carbon coating, forming a carbon coating layer on the surface of the intermediate product by using a carbon material, and sintering to obtain the composite material. The three-dimensional porous silicon skeleton is filled with nano Si, on one hand, the micron porous silicon skeleton can effectively relieve the volume expansion problem caused by insertion and separation of lithium ions (Li < + >) in the charging and discharging process; and on the other hand, the nanometer Si is filled in the micron porous Si framework, so that the compaction density of the negative electrode material can be effectively improved, and the volume energy density is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a high compaction density porous silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] With the popularity of pure electric vehicles and plug-in hybrid vehicles, new requirements have been put forward for the development of lithium-ion batteries. Among them, high capacity and long life are the core issues that have attracted much attention. Graphite-based negative electrode materials have been commercialized due to their long life and high first efficiency (ICE), but their theoretical capacity (372mAh / g) is not enough to meet the growing demand for energy storage. Silicon (Si) has an ultra-high theoretical capacity (3579mAh / g) and a suitable operating voltage (~0.4V), and is considered to be one of the most promising negative electrode materials for lithium-ion batteries. However, Si-based negative electrode materials have the following problems: First, during the charge and discharge process, the volume expansion of Si is as high as 300%, causing the electrode material to pulverize, causing electrochemical failure, and a sharp drop in capacity and cycle life; Second, since Si is a semiconductor in its natural state, each Si atom has four electrons in the outer layer to form a stable chemical bond with the adjacent silicon atoms, and the conductivity of Si material is poor.

[0003] Nano-sizing of Si can effectively alleviate the problem of pulverization and crushing caused by volume expansion, and improve reaction kinetics and rate performance. However, the high specific surface area of ​​nanomaterials has problems such as low compaction density, low ICE and low volume energy density. At the same time, its expensive cost also makes it difficult to promote nano Si. Micron Si has the advantages of high compaction density, low surface area and low cost. On this basis, the porous structure prepared by microstructure design is conducive to alleviating a series of problems such as volume expansion of Si during lithium storage, and then carbon filling or carbon coating is performed to increase its conductivity and stability. However, a large number of pores will also lead to an increase in the specific surface area of ​​the material and a decrease in the compaction density. Therefore, it is urgent to prepare a micron-scale porous silicon-carbon composite material with high cycle stability, high compaction density and low cost.

[0004] CN107507972A discloses a method for preparing a silicon-carbon negative electrode material, comprising: using silicon alloy powder as a raw material, pickling, etching the remaining metals in the silicon alloy powder except silicon, to obtain porous silicon; carbon coating the porous silicon to form a silicon-carbon precursor; and carbonizing the silicon-carbon precursor to obtain a silicon-carbon negative electrode material. However, the porous structure inside the silicon-carbon negative electrode material causes the negative electrode material to have a low compaction density, which in turn leads to a decrease in volume energy density.

[0005] CN115548300A invented a porous silicon-based composite material, which has a core-shell structure, including a silicon-based material as a core, and a porous layer and a carbon coating layer sequentially coated on the outer surface of the core, wherein the porous layer is silicon, or a mixture of silicon and metal, and the pores of the porous layer are filled with carbon material. However, due to the high specific surface area, the silicon-based composite material has problems such as increased side reactions, reduced ICE, and reduced volume energy density caused by low compaction density. Therefore, a porous silicon-carbon composite material with high compaction density is urgently needed. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of existing silicon-based alloys as negative electrode materials, low compaction density and high specific surface area (nano Si-based negative electrode) and electrode crushing due to huge volume expansion during the cycle, and to provide a method for preparing a high compaction density porous silicon-carbon composite material.

[0007] Another object of the present invention is to provide a high compaction density porous silicon-carbon composite material prepared by the preparation method.

[0008] Another object of the present invention is to provide an application of a high compaction density porous silicon-carbon composite material.

[0009] The technical solution adopted to achieve the purpose of the present invention is:

[0010] A method for preparing a high compaction density porous silicon-carbon composite material comprises the following steps:

[0011] Step 1, performing dealloying treatment on the micron silicon-based material to obtain a porous silicon skeleton;

[0012] Step 2, performing pore filling, filling the pores formed in the silicon-based material with nano-silicon material to obtain an intermediate product;

[0013] Step 3, performing carbon coating, forming a carbon coating layer on the surface of the intermediate product with carbon material, and obtaining a composite material after sintering.

[0014] In the above technical solution, the micron silicon-based material in step 1 is one or more of aluminum silicon, magnesium silicon or iron silicon. Preferably, the average particle size D50 of the silicon-based material is 1-50 μm, preferably 1-10 μm. Preferably, the Si content in the silicon-based material is 12% to 50%;

[0015] The dealloying treatment is selected from one or both of pickling and etching treatments and alkaline etching treatments, preferably pickling and etching treatment, more preferably, the acid for the pickling and etching treatment is selected from one or more of hydrochloric acid, sulfuric acid, and hydrofluoric acid, most preferably hydrochloric acid.

[0016] In the above technical solution, the nano-silicon filling material in step 2 includes nano-silicon, and the average particle size D50 of the nano-silicon is 1-100 nm, preferably 20-80 nm.

[0017] In the above technical solution, in step 2, the porous silicon skeleton, nano-silicon and dispersant are mixed, uniformly dispersed in the porous Si material by spray drying, and then heat treated to obtain an intermediate product;

[0018] Preferably, the weight ratio of the porous silicon skeleton to the nano-silicon is (8-2):1, preferably 3:1;

[0019] Preferably, the inlet air temperature during spray drying is 150°C-250°C, preferably 170°C;

[0020] Preferably, the heat treatment conditions include: a temperature of 750-1200° C., preferably 800-900° C.; and a heat preservation time of 1-10 h, preferably 3-5 h.

[0021] In the above technical solution, in the step 3, the intermediate product and the carbon source are sequentially mixed, carbonized and heat-treated under the conditions of an inert gas and an optional solvent;

[0022] Preferably, the weight ratio of the intermediate product to the carbon source is 10:(1-3);

[0023] Preferably, the carbon material is selected from one or more of asphalt, phenolic resin, glucose, sucrose, dopamine, resorcinol, and graphene;

[0024] Preferably, the conditions of the carbonization process include: a temperature of 750-1200° C., preferably 800-1000° C.; and a heat preservation time of 1-10 h, preferably 3-5 h.

[0025] Another aspect of the present invention provides a high compaction density porous silicon-carbon composite material prepared by the preparation method.

[0026] Another aspect of the present invention provides an application of the high compaction density porous silicon-carbon composite material or the composite material prepared by the preparation method in a lithium ion battery.

[0027] Another aspect of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the high compaction density porous silicon carbon or the composite material obtained by the preparation method.

[0028] Another aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate.

[0029] In the above technical solution, the reversible capacity of the lithium-ion battery is greater than 1800 mAh / g;

[0030] And / or the capacity retention rate of the lithium-ion battery after 100 cycles is greater than 70%.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The present invention fills nano-Si in the three-dimensional porous silicon skeleton. On the one hand, the micron porous silicon skeleton can effectively alleviate the lithium ion (Li + )’s insertion and removal; on the other hand, nano-Si filling in the micron porous Si skeleton can effectively increase the compaction density of the negative electrode material, thereby significantly increasing the volume energy density; Nano-Si has a larger specific surface area and can provide more reaction sites, thus improving the rate performance of the material. At the same time, it can alleviate the volume expansion during lithium storage and improve the stability of the structure. The micron Si porous skeleton has a larger particle size, fewer interface reactions, and a higher compaction density than nano-Si. The porous micro-nano silicon-carbon composite material prepared by this invention can maintain good rate performance, structural stability and long cycle performance while significantly improving the compaction density.

[0033] In addition, carbon coating can not only effectively improve the conductivity of silicon-based materials, but also alleviate the volume expansion of silicon particles during charging and discharging. The carbon coating can prevent direct contact between silicon and electrolyte, thereby reducing side reactions such as the accumulation of solid electrolyte interface film (SEI) and improving electrochemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The figure shows the characterization of the composite prepared in Example 2, wherein: Figure 1 (a) is Al 80 Si 20 SEM image of original silicon-based alloy powder, Figure 1 (b) is a SEM image of the micron porous silicon skeleton obtained in step 1. Figure 1 (c) is a SEM image of 50 nm Si filled in the micron porous silicon obtained in step 2. Figure 1 (d) is the SEM image of the intermediate product in step 3 after carbon coating.

[0035] Figure 2 The SEM cross-sectional image of the negative electrode sheet is shown, where: Figure 2 (a) is Al 80 Si 20 Cross-sectional view of the negative electrode sheet prepared by the porous silicon skeleton obtained by dealloying. Figure 2(b) is a cross-sectional view of the negative electrode sheet prepared from the high compaction density porous silicon-carbon composite material obtained in Example 2.

[0036] Figure 3 Shown are the XRD characterization diagrams of the corresponding composites obtained in each step of Example 2.

[0037] Figure 4 The electrochemical performance comparison diagram of the product obtained in Example 2 is shown, wherein: Figure 4 (a) is Al 80 Si 20 Comparison of the cycle performance of the silicon-carbon composite obtained by dealloying treatment and preparation. Figure 4 (b) is a comparison chart of the rate performance of the two. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] A high compaction density porous silicon-carbon composite material is prepared by the following steps:

[0040] Step 1, preparing a three-dimensional porous silicon skeleton;

[0041] The micron-sized silicon-based alloy powder is placed in a container and subjected to a dealloying treatment to obtain a three-dimensional porous silicon skeleton. The micron-sized silicon-based material is one or more of aluminum silicon, magnesium silicon or iron silicon. Preferably, the average particle size D50 of the silicon-based material is 1-50 μm, preferably 1-10 μm. Preferably, the Si content in the silicon-based material is 12% to 50%. The etching solution can be selected from one or both of acid washing or alkaline washing. The acid washing can be selected from one or more of hydrochloric acid, sulfuric acid and hydrofluoric acid. Preferably, hydrochloric acid etching is used, and the concentration of hydrochloric acid is selected from 1 mol / L to 4 mol / L. The alkaline washing can be selected from one or more of potassium hydroxide and sodium hydroxide.

[0042] Step 2, filling nano-Si particles into micron porous silicon;

[0043] The nano-Si particles and the dispersant are mixed in a mass ratio of (8-2):1 and dispersed evenly, and then porous silicon is added and dispersed evenly, and the nano-Si is dispersed evenly in the porous Si material by spray drying, and then heat treated to obtain an intermediate product; wherein the average size D50 of the nano-Si is 1-100nm; the spray drying inlet temperature is 150℃-200℃, and the feed rate is 1mL / min-10mL / min. The heat treatment conditions include: temperature of 750-1200℃; insulation time of 1-10h.

[0044] Step 3, carbon-coating the intermediate product to obtain a silicon-carbon composite material precursor;

[0045] The intermediate product is mixed with the selected carbon source and stirred evenly, and then dried and cured to obtain a silicon-carbon composite material precursor. The silicon-carbon composite material precursor is sintered at high temperature to obtain the three-dimensional porous silicon-carbon composite material; the high-temperature sintering heating rate is 1-10°C / min, the insulation temperature is 700-1200°C, and the insulation time is 1-10h.

[0046] The dispersant used in filling nano-Si into micron porous silicon is one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone, trimethoxysilane acrylate, and 3-aminopropyltrimethoxysilane; the organic carbon source used in carbon coating is one or more of sucrose, glucose, citric acid, phenolic resin, epoxy resin, asphalt, polyvinyl alcohol, polypyrrole, polypyrrolidone, polyaniline, polyacrylonitrile, polydopamine, and lignin.

[0047] Example 1

[0048] A high compaction density porous silicon-carbon composite material is prepared by the following method:

[0049] Step 1: Al 80 Si 20 (average particle size D50 is 7 μm) was added to HCl (2 mol / L), acid-washed at 40°C for 24 h, filtered and dried to obtain a micron porous Si skeleton.

[0050] Step 2, take 200 mg of nano-Si (20 nm), 200 mg of polyvinyl pyrrolidone (PVP) and dissolve them in 50 ml of deionized water, shake them in an ultrasonic oscillator for 1 hour to disperse them evenly, then add 600 mg of micron porous Si skeleton, continue to shake them in an ultrasonic oscillator for 1 hour, and then stir them on a magnetic stirrer at 40°C for 3 hours. The uniform mixture is spray-dried, wherein the inlet air temperature is 170°C, the outlet air temperature is 110°C, and the feed rate is 5 ml / min. After the end, the collected material is an intermediate product of nanospheres filled in micron porous silicon.

[0051] Step 3, dissolve 30 mg of phenolic resin in 40 ml of alcohol, add the intermediate product obtained in step 2, stir for 3 hours, soak for 3 hours, and cure at 100°C for 24 hours to obtain a silicon-carbon precursor, put it into a tubular furnace, introduce inert gas, heat to 850°C at 5°C / min and keep warm for 3 hours, and naturally cool to room temperature to obtain a high compaction density porous silicon-carbon composite material.

[0052] Example 2

[0053] A high compaction density porous silicon-carbon composite material is prepared by the following method:

[0054] Step 1: Al 80 Si 20 (average particle size D50 is 7 μm) was added to HCl (2 mol / L), and after acid washing at 40°C for 24 h, it was filtered and dried to obtain a micron porous Si skeleton. Its XRD pattern is shown in Figure 3 shown.

[0055] Step 2, take 200 mg of nano-Si (50 nm), 200 mg of polyvinyl pyrrolidone (PVP) and dissolve them in 50 ml of deionized water, shake them in an ultrasonic oscillator for 1 hour to disperse them evenly, then add 600 mg of micron porous Si skeleton, continue to shake them in an ultrasonic oscillator for 1 hour, and then stir them on a magnetic stirrer at 40°C for 3 hours. The uniform mixture is spray-dried, wherein the inlet air temperature is 170°C, the outlet air temperature is 110°C, and the feed rate is 5 ml / min. After the end, the collected material is an intermediate product of nanospheres filled in micron porous silicon.

[0056] Step 3, dissolve 30 mg of phenolic resin in 40 ml of alcohol, add the intermediate product obtained in step 2, stir for 3 hours, soak for 3 hours, and cure at 100°C for 24 hours to obtain a silicon-carbon precursor, put it into a tube furnace, pass inert gas, heat it to 850°C at 5°C / min and keep it warm for 3 hours, and naturally cool it to room temperature to obtain a high compaction density porous silicon-carbon composite material. The XRD patterns of the products of each step are as follows: Figure 3 shown.

[0057] SEM images of various materials during the preparation process are shown in Figure 1 (a)- Figure 1 As shown in (d), the high compaction density porous silicon-carbon composite material includes a three-dimensional porous skeleton, a filling layer and a coating layer, wherein the three-dimensional porous skeleton is a three-dimensional porous silicon skeleton, the filling layer is nano-Si particles uniformly dispersed in the porous silicon skeleton, and the coating layer is a carbon coating layer.

[0058] Embodiment 3:

[0059] The high compaction density porous silicon-based composite material in this embodiment is different from that in Embodiment 1 in that:

[0060] The material Al selected in step 1 80 Si 20 Change to Al 60 Si 40 (The size is the same as in Example 1) to obtain micron porous Si skeletons with different porosities and pore sizes.

[0061] Embodiment 4:

[0062] The high compaction density porous silicon-based composite material in this embodiment is different from that in Embodiment 1 in that:

[0063] The material Al selected in step 1 80 Si 20 Change to Al 60 Si 40 (The size is the same as that of Example 1), and micron porous Si skeletons with different porosities and pore sizes are obtained. In step 2, the mass ratio of micron porous Si skeleton: dispersant: nano-Si = 6:2:2 is changed to 8:1:1.

[0064] Comparative Example 1:

[0065] The preparation method provided in Example 1 is adopted, except that:

[0066] Only step 1 is performed for the preparation of a micron three-dimensional porous framework.

[0067] Comparative Example 2:

[0068] The preparation method provided in Example 1 is adopted, except that:

[0069] Only the preparation of the 1 μm three-dimensional porous framework was performed, and Al 80 Si 20 Change to Al 60 Si 40 .

[0070] Comparative Example 3:

[0071] Micron Si balls (average particle size D50 is 7 μm) are used without etching, filling and coating treatment.

[0072] Comparative Example 4:

[0073] Nano-Si spheres (average particle size D50 is 50 nm) are used without etching, filling and coating treatment.

[0074] The embodiments of the present invention were tested by the following test methods:

[0075] The high compaction density porous silicon-carbon composite material of the present invention is used to compare the comparative examples without etching, filling, and carbon coating, that is, the various parameters of the porous silicon skeleton and the nano-Si filled therein, as well as the electrochemical performance, so as to further highlight the advantages of the cycle performance retention rate of the present patent. Silicon balls with different filling densities are prepared by adjusting the doping ratio and the particle size of the filled nano-Si in each step, thereby preparing negative electrode sheets with different compaction densities, thereby achieving the purpose of optimizing material performance.

[0076] In order to further verify the electrochemical properties of the porous silicon-based composite material provided in this application, such as the cycle performance and rate performance, the specific structure of the negative electrode prepared from the porous silicon-based composite material obtained in the above example is as follows: the negative electrode material, the conductive agent carbon black (Super P), and the polyacrylic acid (PAA) are mixed in a solvent pure water at a mass ratio of 6:2:2, and slurried to control the solid content at 45%, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet. The cross-sectional view of the negative electrode sheet is shown in FIG. Figure 2 shown. Figure 2 (a) shows a cross-sectional view of the negative electrode sheet made of porous silicon skeleton. The compaction density is calculated to be 0.75 g / cm 3 ; Figure 2 (b) is a cross-sectional view of the negative electrode sheet prepared after the intermediate product is carbon-coated (i.e., the high compaction density porous silicon-carbon composite material obtained in Example 2), and its compaction density is 1.28 g / cm 3 Compared with the porous silicon skeleton, the compaction density is significantly improved, and through Figure 4 It can be obtained that the cycle and rate performance are also significantly improved. The electrolyte used is 10% fluoroethylene carbonate (FEC) additive added to 1M LiPF6 / EC:DEC (1:1Vol%) electrolyte. The assembly of the battery needs to be in a glove box filled with high-purity argon. The required materials are 2025 type positive and negative electrode shells, electrode sheets, Celgard 2400 diaphragms, metal lithium sheets with a diameter of 18mm and a thickness of 1mm, stainless steel gaskets with a diameter of 18mm, stainless steel springs with a diameter of 18mm and electrolytes. The instrument model used in this patent is Neware BTS4008, with a test voltage range of 0.01-1.5V. The current density of the first three cycle tests is 0.2A / g, and the subsequent ones are 0.5A / g. The cycle performance and rate performance of the material are tested at the same time.

[0077] The test results are as follows Figure 4 (a) and Figure 4 As shown in (b), the cycle performance and rate performance of the lithium ion battery based on the final product of Example 2 and the porous silicon-based composite material obtained in Comparative Example 1.

[0078] Table 1 Performance of each embodiment and comparative example

[0079]

[0080] As can be seen from Table 1, the porous silicon-carbon composite material prepared by the method described in this application can significantly improve the compaction density of the negative electrode material by changing the preparation conditions, such as the filling nano-Si size, doping ratio, etc., thereby increasing the volume energy density and significantly improving the cycle performance. 80 Si 20The three-dimensional porous micron-Si skeleton obtained by etching is filled with nano-Si with a particle size of 50nm, and the compaction density can reach 1.28g / cm 3 Compared with the compaction density of comparative example 1 without nano-silicon filling (0.75 g / cm 3 ), the compaction density of Example 2 is greatly improved. At the same time, the reversible capacity is increased from 1004.63mAh / g in Comparative Example 1 to 2113.25mAh / g in Example 2, and the capacity retention rate after 100 cycles is as high as 96%, which is much higher than 34.3% in Comparative Example 1. The variable between Example 2 and Example 1 is the change in the size of the nano-Si filled during self-assembly. It can be seen from the table that the nano-Si filled with different particle sizes has a higher compaction density than Comparative Example 1, and the cyclic stability performance is improved to varying degrees. The porous silicon skeleton used in Examples 3 and 4 is composed of Al 60 Si 40 Prepared by etching, due to the silicon content compared to Al 80 Si 20 The pores left by the etched silicon skeleton are reduced, and the nano-Si particles cannot enter the porous silicon pores well. Therefore, the dispersion ratio of the porous silicon skeleton and the nano-Si is used as a variable for comparison. In Example 3, the nano-Si particle input ratio is high, and the compaction density after carbon coating is also relatively high, which can reach 1.32g / cm 3 , which are higher than the unfilled comparative example 2. And the capacity retention rates of the two after 100 cycles are 93% and 95% respectively, which are much higher than 41% of comparative example 2.

[0081] Comparative Example 3 is a micron Si ball (average particle size D50 is 7 μm) without processing. It can be seen from the table that its compacted density can reach 1.22 g / cm 3 However, the cycle stability of the assembled battery is extremely poor, and the capacity retention rate after 100 cycles is only 23%. Comparative Example 4 is a nano-Si ball (average particle size D50 is 50nm) without processing, and its compaction density is only 0.53g / cm 3 , but the cycle stability is good, and the capacity retention rate reaches 58% after 100 cycles. Comprehensive comparison, through this patent, the three-dimensional porous silicon skeleton is used for in-situ self-assembly and carbon coating, and the compaction density can reach 1.28g / cm 3 After 100 cycles, the capacity retention rate is as high as 96%. While the compaction density is greatly improved, the cycle performance is also improved.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high compaction density porous silicon-carbon composite material, characterized in that: The following steps are involved: Step 1, performing dealloying treatment on the micron silicon-based material to obtain a porous silicon skeleton; Step 2, performing pore filling, filling the pores formed in the silicon-based material with nano-silicon material to obtain an intermediate product; Step 3, performing carbon coating, forming a carbon coating layer on the surface of the intermediate product with carbon material, and obtaining a composite material after sintering.

2. The preparation method according to claim 1, characterized in that The micron silicon-based material in step 1 is one or more of aluminum silicon, magnesium silicon or iron silicon. Preferably, the average particle size D50 of the silicon-based material is 1-50 μm, preferably 1-10 μm. Preferably, the Si content in the silicon-based material is 12% to 50%; The dealloying treatment is selected from one or both of pickling and etching treatments and alkaline etching treatments, preferably pickling and etching treatment, more preferably, the acid for the pickling and etching treatment is selected from one or more of hydrochloric acid, sulfuric acid, and hydrofluoric acid, most preferably hydrochloric acid.

3. The preparation method according to claim 1, characterized in that: The nano-silicon filling material in step 2 includes nano-silicon, and the average particle size D50 of the nano-silicon is 1-100 nm, preferably 20-80 nm.

4. The preparation method according to claim 1, characterized in that: In the step 2, the porous silicon skeleton, nano-silicon and dispersant are mixed, uniformly dispersed in the porous Si material by spray drying, and then heat treated to obtain an intermediate product; Preferably, the weight ratio of the porous silicon skeleton to the nano-silicon is (8-2):1, preferably 3:1; Preferably, the inlet air temperature during spray drying is 150°C-250°C, preferably 170°C; Preferably, the heat treatment conditions include: a temperature of 750-1200° C., preferably 800-900° C.; and a heat preservation time of 1-10 h, preferably 3-5 h.

5. The preparation method according to claim 1, characterized in that: In the step 3, the intermediate product and the carbon source are sequentially mixed, carbonized and heat-treated under the conditions of an inert gas and an optional solvent; Preferably, the weight ratio of the intermediate product to the carbon source is 10:(1-3); Preferably, the carbon material is selected from one or more of asphalt, phenolic resin, glucose, sucrose, dopamine, resorcinol, and graphene; Preferably, the conditions of the carbonization process include: a temperature of 750-1200° C., preferably 800-1000° C.; and a heat preservation time of 1-10 h, preferably 3-5 h.

6. A high compaction density porous silicon-carbon composite material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the high compaction density porous silicon-carbon composite material according to claim 6 or the composite material prepared by the preparation method according to any one of claims 1 to 5 in a lithium ion battery.

8. A negative electrode plate, characterized in that: The negative electrode plate comprises the high compaction density porous silicon carbon as described in claim 6 or a composite material prepared by the preparation method as described in any one of claims 1-5.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 8.

10. The lithium ion battery according to claim 9, characterized in that The reversible capacity of the lithium ion battery is greater than 1800 mAh / g; And / or the capacity retention rate of the lithium-ion battery after 100 cycles is greater than 70%.

Citation Information

Patent Citations

  • Preparation method of silicon-carbon cathode material, silicon-carbon cathode material and lithium ion battery

    CN107507972A

  • Porous silicon-based composite material, preparation method and application thereof, negative pole piece and lithium ion battery

    CN115548300A

  • Porous silicon-based composite material and preparation method thereof, and application of porous silicon-based composite material

    CN110336003A

  • High-tap-density porous silicon-carbon composite material, preparation method thereof and application of high-tap-density porous silicon-carbon composite material to negative electrode of lithium ion battery

    CN113178552A

  • Three-dimensional porous silicon-carbon composite negative electrode material and drying equipment for preparation

    CN116845205A

Cited By

  • High-rate silicon carbon material and preparation method thereof

    CN121063537A

  • Modified silicon-carbon negative electrode material based on non-carbon-based porous skeleton and preparation method and application thereof

    CN121416444A